Insight Into the Beneficial Role of Lactiplantibacillus plantarum Supernatant Against Bacterial Infections, Oxidative Stress, and Wound Healing in A549 Cells and BALB/c Mice - Dubey, Ashish Kumar; Podia, Mansi; Priyanka,; Raut, Sachin; Singh, Sanpreet; Pinnaka, Anil Kumar; Khatri, Neeraj (Frontiers in Pharmacology, 2021)
Lactiplantibacillus plantarum MTCC 2621 is a well characterized probiotic strain and is reported to possess many health benefits. However, wound healing potential of this probiotic is yet to be explored. Here, we have assessed antibacterial, antioxidant, and wound healing activities of cell-free supernatant of Lactiplantibacillus plantarum MTCC 2621 (Lp2621). Lp2621 exhibited excellent antibacterial activity against the indicator bacteria in agar well diffusion assay. Lp2621 did not show any hemolytic activity. Safety of Lp2621 gel was established using skin irritation assay in BALB/c mice and no dermal reactions was observed. The supernatant showed 60-100% protection of A549 cells against H2O2-induced stress. In the scratch assay, Lp2621 accelerated wound healing after 24h of treatment. Percent wound healing was significantly higher in cells treated with Lp2621 at 18-24h post-treatment. In an excision wound healing in mice, topical application of Lp2621 gel showed faster healing as compared to the vehicle- and betadine-treated groups. Similar wound healing activity was observed in wounds infected with Staphylococcus aureus. Histological examination revealed better wound healing in Lp2621-treated mice. Topical treatment of the wounds with Lp2621 gel resulted in upregulation of pro-inflammatory cytokine IL-6 in the early phase of wound healing and enhanced IL-10 expression in the later phase. These findings unveil a protective role of Lp2621 against bacterial infection, oxidative stress and wound healing.